Exchange Rate Volatility and U.S. Auto-Industry Exports: A Panel Cointegration Approach - Avsar, Veysel; Turkcan, Kemal (International Journal of Economics and Financial Issues, 2013)
Intermediate goods are often neglected in the empirical studies of the impact of exchange rate volatility on bilateral trade flows. Using import unit values of 58 motor vehicle products and 193 auto-parts, which are classified by the 10-digit level of Harmonized Tariff Schedule (HTS), this study examines the impact of exchange rate volatility on the U.S. automotive industry exports and imports (both motor-vehicle products and auto-parts) from 37 major trading partners for the period of 1996.01 to 2008.4 by using panel data cointegration techniques. We obtain substantial heterogeneity in terms of the impact of exchange rate volatility for final and intermediate goods. We also find support for the positive hypothesis that exchange rate volatility may lead to greater levels of trade. Keywords: Exchange rate volatility; the U.S. auto-parts industry; Fragmentation; Panel econometrics JEL Classifications: C33; F14; F31; F40